Genetic recombination in plant-infecting messenger-sense RNA viruses: overview and research perspectives - Bujarski, Jozef J. (Frontiers in Plant Science, 2013)
RNA recombination is one of the driving forces of genetic variability in (+)-strand RNA viruses. Various types of RNA-RNA crossovers were described including crosses between the same or different viral RNAs or between viral and cellular RNAs. Likewise, a variety of molecular mechanisms are known to support RNA recombination, such as replicative events (based on internal or end-to-end replicase switchings) along with nonreplicative joining among RNA fragments of viral and/or cellular origin. Such mechanisms as RNA decay or RNA interference are responsible for RNA fragmentation and trans-esterification reactions which are likely accountable for ligation of RNA fragments. Numerous host factors were found to affect the profiles of viral RNA recombinants and significant differences in recombination frequency were observed among various RNA viruses. Comparative analyses of viral sequences allowed for the development of evolutionary models in order to explain adaptive phenotypic changes and co-evolving sites. Many questions remain to be answered by forthcoming RNA recombination research. (i) How various factors modulate the ability of viral replicase to switch templates, (ii) What is the intracellular location of RNA-RNA template switchings, (iii) Mechanisms and factors responsible for non-replicative RNA recombination, (iv) Mechanisms of integration of RNA viral sequences with cellular genomic DNA, and (v) What is the role of RNA splicing and ribozyme activity. From an evolutionary stand point, it is not known how RNA viruses parasitize new host species via recombination, nor is it obvious what the contribution of RNA recombination is among other RNA modification pathways. We do not understand why the frequency of RNA recombination varies so much among RNA viruses and the status of RNA recombination as a form of sex is not well documented.